Intestinal obstruction mimicking intra-abdominal hemorrhage in a teenager with familial thrombocytopenia: a case report - Sutaryo Sutaryo; Kaiser Ali; Untung Widodo; Nunik Agustriyani; Edy Moeljono; Mark Belletrutti (Indonesian Pediatric Society Publishing House, 2016)
Inherited bleeding disorders are a heterogeneous group of disease that is complicated by hemorrhagic episodes, spontaneous, and post- traumatic. Included in this category of conditions are Familial Thrombocytopenias (FT). FT are a heterogeneous group of inherited disorders that vary in severity with regard to the degree of reduction in platelet counts and in expression of bleeding manifestations. As in acquired thrombocytopenias, FT patients are at risk for hemorrhagic complications. Rarely, patients with inherited non-thrombocytopenia bleeding disorders can develop complications of acute abdomen 1,2 which present as intraabdominal hemorrhage. We report a case of intestinal obstruction mimicking an uncomplicated intraabdominal hemorrhage in a teenager with FT.